2006
DOI: 10.1111/j.1472-8206.2005.00389.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin cytotoxicity in human leukemia cells: relation with its pro‐oxidant effect

Abstract: Melatonin has a variety of functions in human physiology and is involved in a number of pathological events including neoplastic processes. The tissue protective actions of melatonin are attributed to its antioxidant activity though, under certain conditions, melatonin might also exert oxidant effects, particularly in cancer cells. This study evaluated the effects of 10(-5) and 10(-3) m concentrations of melatonin on human leukemia cells. Moderate cytotoxic effects of melatonin at 10(-3) m concentrations were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
62
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 37 publications
6
62
2
Order By: Relevance
“…Whereas in normal cells melatonin and its metabolites act as efficient radical scavengers (63), it has been suggested that changes in the oxidative status account for the ability of melatonin to induce apoptosis in cancer cells (62,64,65). In this regard, a correlation between the increase in ROS production and the induction of melatonin-driven apoptosis has been reported in several cell lines (66). Consistent with this evidence, we have preliminarily observed a reduction in the melatonin cytotoxic effect by pretreating RMS cells with vitamin E (data not shown), a lipid-soluble antioxidant molecule.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas in normal cells melatonin and its metabolites act as efficient radical scavengers (63), it has been suggested that changes in the oxidative status account for the ability of melatonin to induce apoptosis in cancer cells (62,64,65). In this regard, a correlation between the increase in ROS production and the induction of melatonin-driven apoptosis has been reported in several cell lines (66). Consistent with this evidence, we have preliminarily observed a reduction in the melatonin cytotoxic effect by pretreating RMS cells with vitamin E (data not shown), a lipid-soluble antioxidant molecule.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence for a direct effect rests on the fact that melatonin can act as a powerful free radical scavenger in isolated cell-free systems (Beyer et al, 1998;Tan et al, 2002). Skaper et al (1999), Cheung (2003) There are however reports that melatonin can act in a prooxidant in such systems Buyukavci et al, 2006). Melatonin is present within brain at a concentration (around 4 pM) that is only 5% of that found in serum , and -unless it were to be highly concentrated in a localized area -can make little scavenging contribution in comparison to predominant antioxidant species such as glutathione (present in millimolar amounts) and a-tocopherol (5 mM, Sanchez-Moreno et al, 2004).…”
Section: Melatonin As An Anti-oxidantmentioning
confidence: 99%
“…Protective effect of melatonin against cytotoxic effect of O 2 molecule has also been reported in cerebellar granular cells [50,51]. However, contradictory reports have showed that melatonin has some pro-oxidant capability [49,[52][53][54]. Studies in cell lines have showed that the pro-oxidant capacity of melatonin could be utilized in the treatment of cancer [54][55][56][57].…”
Section: Melatonin: An Antioxidantmentioning
confidence: 93%